Are scale leaves essencial in temperate-cold climates? An evaluation in tree species from temperate rainforests of South America - Sosa, Claudia Maricel (2023)
The development of scaly buds (= cataphylls) has been traditionally associated with seasonally cold climates, although only few species from the southern hemisphere were investigated in this regard. The present work focuses on apical and axillary buds of seven tree species native to the South-American Temperate Rainforests (STR). Due to differences in the lineages from which these species derived, high levels of inter-specific variation in bud structure were expected. Apical and axillary buds were dissected under stereomicroscope, and the sizes of their parent shoots were evaluated. Cataphylls and leaf primordia were counted, and the presence of colleters and/or trichomes registered. Both intraand inter-specific variations in bud structure were found. The apical buds were scaly in two out of seven species, and naked in the other species. Axillary buds were scaly in all but one species. In general terms, larger shoots developed buds with more organs. The presence of colleters (in four species) was not restricted to those buds lacking an outer cover of cataphylls. Further studies should focus on the relevance at a broader scale of colleters and trichomes as protective structures in tree buds.